2019
DOI: 10.3390/en12060971
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Combustion Stability of Diesel-Methanol and Diesel-Ethanol in a Dual Fuel Engine

Abstract: The co-combustion of diesel with alcohol fuels in a compression ignition dual fuel engine is one of the ways of using alternative fuels to power combustion engines. Scientific explorations in this respect should not only concern the combustion process in one engine cycle, which is most often not representative for a longer engine life, but should also include an analysis of multiple cycles, which would allow for indicating reliable parameters of engine operation and its stability. This paper presents experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…For the mid-load condition, the substitution was increased to 63%; however, for low and high loads, higher ethanol fractions could not be used because of insufficient ignition energy at low loads and high values of pressure rise under high loads [7]. Similar results were obtained by other authors; all of them showed that the share of ethanol has a positive effect on soot emissions, while there are different opinions regarding NO x emissions [8][9][10][11]. On the one hand, ethanol reduces the temperature on the compressed load due to the high heat of vaporization.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…For the mid-load condition, the substitution was increased to 63%; however, for low and high loads, higher ethanol fractions could not be used because of insufficient ignition energy at low loads and high values of pressure rise under high loads [7]. Similar results were obtained by other authors; all of them showed that the share of ethanol has a positive effect on soot emissions, while there are different opinions regarding NO x emissions [8][9][10][11]. On the one hand, ethanol reduces the temperature on the compressed load due to the high heat of vaporization.…”
supporting
confidence: 69%
“…Combustion process of blend was characterized by high increase in COV of IMEP. Already for 19% ethanol, energetic fraction COVIMEP exceeded 5%, which is a limit value for industrial engines [10]. In case of dual fuel technology, the COV of IMEP was below 5% and its maximal value was reached for 50% of ethanol fraction, equal to 3%.…”
Section: Results Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…where N is the cycle index and p max is the mean value of maximum pressure of N cycle p maxi . One of the indicators enabling the assessment of the stability of operation of an internal combustion engine may also be the probability density of selected parameters of its operation [29]. The function that allows us to express the probability of obtaining or occurrence of a specific value of the analyzed parameter is the probability density function.…”
Section: Test Methods and Conditionsmentioning
confidence: 99%